2006
DOI: 10.1021/es0523845
|View full text |Cite
|
Sign up to set email alerts
|

The Global Atmospheric Environment for the Next Generation

Abstract: Air quality, ecosystem exposure to nitrogen deposition, and climate change are intimately coupled problems: we assess changes in the global atmospheric environment between 2000 and 2030 using twenty-five state-of-the-art global atmospheric chemistry models and three different emissions scenarios. The first (CLE) scenario reflects implementation of current air quality legislation around the world, whilst the second (MFR) represents a more optimistic case in which all currently feasible technologies are applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
241
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(254 citation statements)
references
References 22 publications
11
241
2
Order By: Relevance
“…There is a growing body of evidence that climate change will have broad negative impacts on the distribution and toxicity of environmental contaminants (Bell et al, 2007;Buckman et al, 2007;Confalonieri et al, 2007;Dentener et al, 2006;Fiala et al, 2003;Hogrefe et al, 2004;Knowlton et al, 2004;Macdonald et al, 2005;Patra et al, 2007;Schiedek et al, 2007;Stevenson et al, 2006). However, many areas merit further examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence that climate change will have broad negative impacts on the distribution and toxicity of environmental contaminants (Bell et al, 2007;Buckman et al, 2007;Confalonieri et al, 2007;Dentener et al, 2006;Fiala et al, 2003;Hogrefe et al, 2004;Knowlton et al, 2004;Macdonald et al, 2005;Patra et al, 2007;Schiedek et al, 2007;Stevenson et al, 2006). However, many areas merit further examination.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Racherla and Adams (2006) project a 5% decline in global tropospheric ozone concentrations in the 2050s from 1990s levels using present day pollutant emission scenarios. Dentener et al (2006) and Stevenson et al (2006) estimated future ozone concentrations for 2030 based on current levels of emissions. They calculated that climate change could reduce global ozone by 0.5-1.0 ppb over the continents and 1-2 ppb over the oceans.…”
Section: Altered Fate and Behavior Of Air Pollutantsmentioning
confidence: 99%
“…An evaluation of the highemissions IPCC SRES A2 emissions scenario showed global July mean surface O 3 increases of about 5 ppb by the year 2030, and 20 ppb by 2100 (Prather et al, 2003). Based on the ensemble mean of 26 global atmospheric chemistry-transport models, Dentener et al (2006) predicted that by 2030 global surface ozone may increase globally by 4.3 AE 2.2 ppb for the IPCC SRES A2 scenario. The same study points out that the SRES A2 scenario, which induces higher pollution levels, would compromise the attainment of any existing air quality standard in most industrialized parts of the world by 2030.…”
Section: T R a C Tmentioning
confidence: 99%
“…Under the SRES A2 scenario, Szopa et al (2006) estimated that by 2030, the O 3 levels in July may increase up to 5 ppb across Europe, due to combined effects of local emission changes added to background O 3 changes. Nevertheless, it should be noticed that this SRES A2 scenario is considered to be a pessimistic one (Dentener et al, 2006). Few studies have been conducted at a regional scale.…”
Section: T R a C Tmentioning
confidence: 99%
“…Waliguan in Qinghai province, China (Deliger and Zhao, 2007). Results from 26 established global atmospheric chemistry-transport models driven by analyzed meteorological fields have shown that global annual mean surface O 3 concentrations will increase by 1.5 ppb (CLE scenario)e4.3 ppb (IPCC SRES A2 scenario) over the period 2000e2030 (Dentener et al, 2006). In China, rapid development of the economy and society and fast urbanization will cause ambient O 3 concentration to rise faster than in other countries due to increasing emissions of trace gases such as nitrogen dioxide and volatile organic compounds.…”
Section: Introductionmentioning
confidence: 99%